A review on building energy efficiency techniques - Al-Ghaili A.M.; Kasim H.; Othman M.; Hassan Z. (Science Publishing Corporation Inc, 2023)
This paper highlights a number of recently published research studies during last five years in order to provide a summary related to latest trends of energy efficiency in the smart buildings technology. It reviews numerous technical methods applied to achieve a high level of Building Energy Efficiency (BEE). In this paper, methods applied to measure the BEE and to predict the energy-use have been considered and reviewed. Furthermore, some other methods discussed in articles which consider retrofitting of interior design of buildings have been taken. One of the most impacts that has been considered is the light control system because it directly affects the energy use. This paper has reviewed different types of techniques that save energy consumptions such as predictive techniques of energy use, Internet of Things (IoT) buildings, light control systems inside buildings, and Quick Response (QR) code based services used to notify occupants for energy-use. It has provided a simple comparison between different techniques used to retrofit the interior design of buildings due to its high importance in saving energy. The paper has also recommended suitability of methods taking into account the existing situation, design, limitations, and conditions of the building being studied. 2018 Authors.